The effect of mother-infant skin - to - skin contact on infant\'s pre - feeding behaviors - M Ali-Akbar; T Safarabadi-Farahani; S Taavoni; H Haghani (Iran University of Medical Sciences, 2011)
Background and Aim: The importance of pre-feeding behaviors in successful breastfeeding and duration of exclusive breastfeeding necessitates the detection of factors influencing these behaviors. The aim of this study was to examine the effect of mother-infant skin-to-skin contact on pre-feeding behaviors of healthy full-term infants of primiparous women.   Materials and Method: This study was a randomized-controlled trial conducted in labor and maternity wards of Shahid Akbar-Abadi hospital in Tehran. One hundred healthy primiparous mother-infant dyads were randomly assigned to receive either skin-to-skin contact (n=50) or routine care (n=50). A demographic information form and The Infant Breastfeeding Assessment Tool was used to collect data. Data were analyzed by SPSS. For testing research hypotheses, Mann-Whitney U test was used.   Results: There was a statistically significant difference between skin-to-skin contact group and routine care group in infant's pre-feeding behaviors including wakefulness (P ≤ 0.001), rooting reflex (P ≤ 0.001), and sucking reflex (P ≤ 0.001).   Conclusion: According to the findings, early skin-to-skin contact after delivery has positive effect on full-term infant's pre-feeding behaviors. These behaviors have been considered to be effective on breast-feeding success and duration of exclusive breast-feeding. It is recommended to implement early skin-to-skin contact after delivery and thereafter.